The complete chloroplast genome sequence of Ficus hirta (Moraceae). Issue 2 (3rd July 2019) - Liu, Yinrong; Chen, Wenna; Li, Fang; Li, Chan; Xie, Xuena; Chao, Zhi; Tian, Enwei
Abstract: The dry root (Radix Fici Hirtae) of Ficus hirta has been used as a traditional herbal medicine in Ling nan regions of China for a long time. As its large market demand, the wild resources of F. hirta have sharply reduced. It is necessary to conduct the study of conservation genetics. However, there is still lack of complete genome information for the research on evolutionary biology, population genetics and phylogeography of this species. Here, we sequenced the complete chloroplast (CP) genome of F. hirta using Next Generation Sequencing technology (NGS). The CP genome of F. hirta is 160, 374 bp in length, which contains a large single-copy (LSC) region of 88, 446 bp, a small sing-copy (SSC) region of 18, 134 bp, and two inverted repeat (IRa and IRb) regions of 26, 897 bp. A total of 130 genes were successfully annotated containing 85 protein-coding genes, 37 tRNA genes and 8 rRNA genes. Phylogenetic analysis support genus Ficus is monophyletic and F. hirta is closely related to F. carica within this genus.